2017
DOI: 10.1002/eet.1752
|View full text |Cite
|
Sign up to set email alerts
|

Using Social Network Analysis to Monitor and Assess the Effectiveness of Knowledge Brokers at Connecting Scientists and Decision‐Makers: An Australian case study

Abstract: Despite growing rhetoric regarding the potential benefits of using knowledge brokers in relation to environmental challenges and decision‐making processes, the evidence in support of such claims is mostly anecdotal. This is, in part, due to the lack of established methods to evaluate the effectiveness and efficiency of knowledge brokers. To address this gap we assess the utility of social network analysis (SNA) to evaluate the effectiveness of knowledge brokers in connecting scientists and decision‐makers. Spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 66 publications
0
63
0
3
Order By: Relevance
“…As such, the Frayme secretariat is uniquely positioned to act as a broker among partners. Other research has found that brokers serve unique roles in that they are able to make personal connections to support new partnerships, span inter-disciplinary and intersectoral boundaries and overcome power differentials within KT networks [19,25]. KT networks interested in bridging interdisciplinary boundaries and creating new avenues for exchange of ideas might benefit from analysing network connections to identify weak ties.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, the Frayme secretariat is uniquely positioned to act as a broker among partners. Other research has found that brokers serve unique roles in that they are able to make personal connections to support new partnerships, span inter-disciplinary and intersectoral boundaries and overcome power differentials within KT networks [19,25]. KT networks interested in bridging interdisciplinary boundaries and creating new avenues for exchange of ideas might benefit from analysing network connections to identify weak ties.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, one-third of survey participants noted that they were involved in projects that were not directly funded by the KT network, but that were the result of partnerships that were created through network membership and three-quarters of respondents described changes in their practice that had resulted through participation in the network. Researchers have identified that knowledge brokers can also successfully grow stakeholder networks in the pursuit of increasing uptake of scientific evidence [25]. In addition, they can enhance stakeholder understanding of the knowledge needs of other network members, including the nature of operating environments allowing for more focused delivery of knowledge exchange [25].…”
Section: Partnership In Knowledge Translationmentioning
confidence: 99%
See 1 more Smart Citation
“…Only with effective, transparent and credible knowledge brokers at the interfaces between different disciplines and societal sectors, decision-makers can be informed and different perspectives comprehensively integrated (Neßhöver et al, 2016;Morin et al, 2017;Sarkki et al, 2019). Network analyses can help to assess knowledge exchange flows within a given network and identify or evaluate knowledge brokers (Toikka, 2010;Crona and Parker, 2011;Weiss et al, 2012;Cvitanovic et al, 2017), as demonstrated by the presented analysis.…”
Section: Nefo As Knowledge Broker and Boundary Organizationmentioning
confidence: 93%
“…One participant said that their role was neither as user, provider, nor producer, but to facilitate connections between all three groups. This example demonstrates that while knowledge brokering can include knowledge dissemination (Lemos et al, 2014;Lomas, 2007), it may also focus primarily on network growth and capacity building (Cvitanovic et al, 2017).…”
Section: Methodsmentioning
confidence: 99%